EFFICACY OF HALF-DOSE PHOTODYNAMIC THERAPY VERSUS HIGH-DENSITY SUBTHRESHOLD MICROPULSE LASER FOR TREATING PIGMENT EPITHELIAL DETACHMENTS IN CHRONIC CENTRAL SEROUS CHORIORETINOPATHY. Issue 4 (April 2022) - Feenstra, Helena M. A.; Hahn, Leo C.; van Rijssen, Thomas J.; Tsonaka, Roula; Breukink, Myrte B.; Keunen, Jan. E. E.; Peters, Petrus J. H.; Dijkman, Greet; Souied, Eric H.; MacLaren, Robert E.; Querques, Giuseppe; Downes, Susan M.; et al.
Abstract : Half-dose photodynamic therapy leads to a significantly larger decrease in the height of the highest macular pigment epithelial detachment compared with high-density subthreshold micropulse laser treatment in chronic central serous chorioretinopathy. Abstract : Purpose: Comparing the effect of half-dose photodynamic therapy and high-density subthreshold micropulse laser treatment on retinal pigment epithelial detachments (PEDs) in chronic central serous chorioretinopathy. Methods: This study included data from the PLACE trial, a prospective randomized controlled trial comparing half-dose photodynamic therapy and high-density subthreshold micropulse laser treatment in chronic central serous chorioretinopathy. Main outcome measurements were changes in both the foveal PED and the highest PED within the macula at baseline compared with first and final evaluation visit. Results: At baseline, a macular PED was detected in 76.9% of patients (123/160), and a PED within 1, 500 µ m from the foveal center in 37.5% of patients (60/160). In the half-dose photodynamic therapy arm (61 patients), there was a significantly larger decrease in the highest macular PED compared with the high-density subthreshold micropulse laser treatment arm (62 patients) at both first and final evaluation visits ( P < 0.001 and P = 0.012, respectively). The decrease of highest foveal PED was significant at first visit ( P = 0.025). Conclusion: Half-dose photodynamic therapy is superior to high-density subthreshold micropulse laser treatment with regard to a statistically significant reduction in the height of macular PEDs in active chronic central serous chorioretinopathy. These findings may also have implications for other diseases within the pachychoroid disease spectrum that can present with PEDs.